Epigallocatechin Gallate Is the Most Effective Catechin Against Antioxidant Stress via Hydrogen Peroxide and Radical Scavenging Activity - He, Jinting; Xu, Lei; Yang, Le; Wang, Xiaofeng (Medical science monitor, 2018)
BACKGROUND Hydrogen peroxide-induced neuronal oxidative stress is a serious threat to the nervous system. Catechins and related compounds are effective radical scavengers that protect against nerve cell damage. MATERIAL AND METHODS Here, we investigated the antioxidant property of various catechins in protecting against hydrogen peroxide, as well as their radical-scavenging activity. RESULTS We found that catechins treatment effectively protected HT22 cells against H₂O₂-induced cell viability by decreasing and attenuating reactive oxidative species production in different proportions. In addition, all tested catechins performed radical scavenging activity, and partially removed the free radicals. Among all investigated catechins, epigallocatechin gallate was the most effective against ROS production and had the strongest radical-scavenging activity. These results suggest that beneficial effects were strongly related with structure of catechins, mainly because of the hydroxyl and galloyl groups. CONCLUSIONS In conclusion, epigallocatechin gallate is the most effective antioxidant polyphenol against hydrogen peroxide and radical-scavenging activity.